The effect of hippotherapy on trunk muscles emg, grasping force and functional mobility changes for person after coma - Aleknavičiūtė-Ablonksė, Vaida; Savenkovienė, Agnė; Mockevičienė, Daiva; Miliūnienė, Lina (Social Welfare: Interdisciplinary Approach, 2016)
The present research has been based on the case study. The changes of balance in trunk muscles, body mobility were evaluated during the hippotherapy sessions. During hypotherapy activities such as touching various parts of the horse’s body (e.g. the neck, flank, back) or reaching for an object (e.g. ball or ring), which involves crossing the midline while maintaining appropriate balance and posture are performed. Positive results were set up in isometric grip strength accordingly in right and in left hands 47 and 2 % and functional mobility in 50%. We found out greater EMG of RA, EO, LT and MF muscles in right vs left side during walking, and RA, LT during riding. We presume that increased grasping muscle strength is related with the increased trunk muscle strength and increased ability to maintain upright position
Keywords: Awakening after coma; trunk muscles; functional mobility; hippotherapy